Ferroptosis and cuproptosis in head and neck squamous cell carcinoma: interconnected mechanisms and therapeutic implications - Liu, Yinan; Li, Yanru (Frontiers in Pharmacology, 2026)
Head and Neck Squamous Cell Carcinoma (HNSCC) is a highly prevalent malignant neoplasm worldwide. Iron and copper metabolism disorder regulate ferroptosis and cuproptosis, two forms of cell death, respectively, and play key roles in the progression and treatment response of HNSCC. Recent studies have shown that these two death pathways have complex interactions, which together affect the malignant progression and tolerance of HNSCC, providing potential targets for its treatment. This review systematically elucidates the interconnected regulatory networks linking ferroptosis and cuproptosis in HNSCC, with particular emphasis on the clinical significance of associated biomarkers for diagnosis and therapy. We further discuss the potential advantages of dual-targeting strategies and critically evaluate current challenges and limitations in translational applications. By providing novel insights into metal ion-dependent cell death mechanisms, this review establishes a theoretical foundation for developing innovative combinatorial therapeutic approaches against HNSCC.